The TAM receptor tyrosine kinases Axl and Mer drive the maintenance of highly phagocytic macrophages - Jiménez-García, Lidia; Mayer, Christopher; Burrola, Patrick G.; Huang, Youtong; Shokhirev, Maxim N.; Lemke, Greg (Frontiers in Immunology, 2022)
Many apoptotic thymocytes are generated during the course of T cell selection in the thymus, yet the machinery through which these dead cells are recognized and phagocytically cleared is incompletely understood. We found that the TAM receptor tyrosine kinases Axl and Mer, which are co-expressed by a specialized set of phagocytic thymic macrophages, are essential components of this machinery. Mutant mice lacking Axl and Mer exhibited a marked accumulation of apoptotic cells during the time that autoreactive and nonreactive thymocytes normally die. Unexpectedly, these double mutants also displayed a profound deficit in the total number of highly phagocytic macrophages in the thymus, and concomitantly exhibited diminished expression of TIM-4, CD163, and other non-TAM phagocytic engulfment systems in the macrophages that remained. Importantly, these previously unrecognized deficits were not confined to the thymus, as they were also evident in the spleen and bone marrow. They had pleiotropic consequences for the double mutants, also previously unrecognized, which included dysregulation of hemoglobin turnover and iron metabolism leading to anemia.